2016
DOI: 10.1017/jog.2016.132
|View full text |Cite
|
Sign up to set email alerts
|

Five decades of strong temporal variability in the flow of Brunt Ice Shelf, Antarctica

Abstract: ABSTRACT. Data showing velocity changes on the Brunt Ice Shelf (BIS), Antarctica, over the last 55 years are presented and analysed. During this period no large-scale calving events took place and the ice shelf gradually grew in size. Ice flow velocities, however, fluctuated greatly, increasing twofold between 1970 and 2000, then decreasing again to previous levels by 2012 after which velocities started to increase yet again. In the observational period, velocity changes in the order of 10% a −1 have commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 29 publications
(64 reference statements)
2
36
0
Order By: Relevance
“…1). In concurrence with these changes, Gudmundsson et al (2017) reported on a new phase of ice-shelf-wide acceleration as surface velocities have increased by up to 10 % per year since 2012. Detailed measurements of these changes have been facilitated by the presence of the Halley 6 Research Station, now located at Halley 6a (see Fig.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…1). In concurrence with these changes, Gudmundsson et al (2017) reported on a new phase of ice-shelf-wide acceleration as surface velocities have increased by up to 10 % per year since 2012. Detailed measurements of these changes have been facilitated by the presence of the Halley 6 Research Station, now located at Halley 6a (see Fig.…”
Section: Introductionmentioning
confidence: 64%
“…8b. In subsequent decades, the BIS gradually readvanced and reestablished contact with the bedrock at the MIR, whilst velocities decreased to pre-1970 levels (Gudmundsson et al, 2017). This cycle of internal dynamical change controlled by calving-induced unpinning and subsequent regrounding at the MIR is arguably not a unique phenomenon, as many ice shelves around Antarctica, and in particular in Dronning Maud Land, are controlled by the presence of one or several pinning points (Matsuoka et al, 2015;Fürst et al, 2015;Favier et al, 2016;Berger et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations